Human talent management control in universities: a bibliometric study - Nuñez Cruz, Carlos Rafael; García Mera, Silvia Magdalena; González Kadashinskaia, Galina Orlandovna (Revista Venezolana de Gerencia, 2025)
The research aims to develop a bibliometric study focused on the control of human talent management in universities as a starting point for a deeper exploration of this topic. The methodology employed the Scopus database and refined the search by applying the PRISMA method. Production, impact, and content indicators were analyzed. The files downloaded in CSV format were processed using the Bibliometrix software on the R Studio platform and VOSviewer. The results showed a productive increase in the topic, especially until the year 2022, with China, the United States, and Australia being the most representative countries. No institutions, resources, or authors with high levels of scientific production were detected. The most frequent keyword was human resource management, and the most significant group concentrated on the terms human resource management, higher education institutions, quality control, and information management. In conclusion, it was demonstrated that, although the topic has been little addressed, it shows a growing trend in the last decade, which constitutes a basis for continuing the study of human talent management in universities.